2020
DOI: 10.1021/acschemneuro.0c00152
|View full text |Cite
|
Sign up to set email alerts
|

A Single Administration of the Atypical Psychedelic Ibogaine or Its Metabolite Noribogaine Induces an Antidepressant-Like Effect in Rats

Abstract: Anecdotal reports and open label case studies in humans indicated that the psychedelic alkaloid ibogaine exert profound anti-addictive effects. Ample preclinical evidence demonstrated the efficacy of ibogaine, and its main metabolite noribogaine, in substance use disorder rodent models. In contrast to addiction research, depression-relevant effects of ibogaine or noribogaine in rodents have not been previously examined. We have recently reported that the acute ibogaine administration induced a long-term increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 57 publications
3
28
0
2
Order By: Relevance
“…In this manner, ibogaine and noribogaine should be considered to explain our results. Although affinities displayed to most of the CNS receptors by ibogaine and noribogaine are low (micromolar range), we estimated high free drug maximum concentrations in rat brain for both substances in brain ( ∼ 3.1-3.5 μ M) 19 . In this regard, noncompetitive antagonism at N-methyl-D-aspartate receptors (NMDA-R) by ibogaine (Ki ∼ 1.01-5.20 μ M 40,[47][48][49][50][51][52][53] ) and in a less extent by noribogaine (Ki ∼ 5.48-31.4 μ M 47,49,53 ) should be considered as a key factor to explain the effects on the gamma band found on this study, since ketamine (a non-competitive NMDA-R antagonist) administration also produces a marked increase in gamma power [54][55][56][57] while decreasing inter-regional gamma coherence 55,57 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In this manner, ibogaine and noribogaine should be considered to explain our results. Although affinities displayed to most of the CNS receptors by ibogaine and noribogaine are low (micromolar range), we estimated high free drug maximum concentrations in rat brain for both substances in brain ( ∼ 3.1-3.5 μ M) 19 . In this regard, noncompetitive antagonism at N-methyl-D-aspartate receptors (NMDA-R) by ibogaine (Ki ∼ 1.01-5.20 μ M 40,[47][48][49][50][51][52][53] ) and in a less extent by noribogaine (Ki ∼ 5.48-31.4 μ M 47,49,53 ) should be considered as a key factor to explain the effects on the gamma band found on this study, since ketamine (a non-competitive NMDA-R antagonist) administration also produces a marked increase in gamma power [54][55][56][57] while decreasing inter-regional gamma coherence 55,57 .…”
Section: Discussionmentioning
confidence: 88%
“…was employed in this work. This dose has the largest effect on sleep and motor behavior 18 and correlates with the high doses involved in shamanic and medicinal uses of ibogaine 19 .…”
Section: Ibogainementioning
confidence: 82%
See 1 more Smart Citation
“…As mentioned in a recent review, there are many unsolved problems regarding the chemistry and neuropharmacology of ibogaine, which are of high importance considering the increased interest of psychedelic compounds as promising experimental therapeutics in neuropsychiatric disorders. Our group has recently published new findings regarding the intriguing neuropharmacology of ibogaine: its ability to induce the expression of neurotrophic factors in the brain, its antidepressive-like effect in rodents models, and the characterization of its unusual oneirogenic psychedelic effects through electrophysiological studies in the rat brain. , From a chemical standpoint, ibogaine and other structurally related iboga alkaloids still lack efficient and scalable enantioselective total syntheses despite the vast amount of outstanding synthetic studies found in the field . Thus, direct extraction from natural sources or semi-synthetic preparations are the methods of choice to obtain ibogaine and related analogues in a preparative scale.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The clinical claims of ibogaine's anti-addictive properties have been recapitulated in numerous rodent models of substance use disorders (SUDs) and depression. [14][15][16][17] Ibogaine has a complex chemical structure where the tryptamine motif is intricately embedded in the isoquinuclidine ring, leading to a polycyclic tryptamine system that defines the iboga alkaloids (Fig. 1a, d).…”
mentioning
confidence: 99%